A duplex current‐reused CMOS LNA with complementary derivative superposition technique. (24th June 2016) - Dai, Ruofan; Zheng, Yunlong; He, Jun; Kong, Weiran; Zou, Shichang
Summary: A duplex current‐reused complementary metal–oxide–semiconductor low‐noise amplifier (LNA) is proposed for 2.5‐GHz application. The duplex current‐reused topology with equivalent three common‐source gain stages cascaded is utilized to fulfil the low‐power consumption and high gain simultaneously. The complementary derivative superposition linearization technique with bulk‐bias control is employed to improve the linearity performance with large‐signal swing and to extend the auxiliary transistors bias‐control range. The proposed LNA is fabricated in a 0.18‐um 1P5M complementary metal–oxide–semiconductor process and consumes a 3.13‐mA quiescent current from a 1.5 V voltage supply. The measurement results show that the proposed LNA achieves power gain of 28.1 dB, noise figure of 1.64 dB, input P1dB and IIP3 of −19.6 dBm and 3.2 dBm, respectively, while the input and output return loss is 19.2 dB and 18.4 dB. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A duplex current‐reused complementary metal–oxide–semiconductor low‐noise amplifier (LNA) is proposed for 2.5‐GHz application. The duplex current‐reused topology with equivalent three common‐source gain stages cascaded is utilized to fulfil the low‐power consumption and high gain simultaneously. The complementary derivative superposition linearization technique with bulk‐bias control is employed to improve the linearity performance with large‐signal swing and to extend the auxiliary transistors bias‐control range.